2021
DOI: 10.1097/mej.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

The association of body temperature with antibiotic therapy and mortality in patients attending the emergency department with suspected infection

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…Consistent with previous reported detailing the association of BTs and mortality in ED patients, 27 we indicated that afebrile status or hypothermia in bacteraemia adults was corresponding to worse prognoses, compared with that of patients with febrile response at bacteraemia onset. We believe that the favourable prognoses of patients with higher iBTs are attributable to increased humoral and cellular immunity.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reported detailing the association of BTs and mortality in ED patients, 27 we indicated that afebrile status or hypothermia in bacteraemia adults was corresponding to worse prognoses, compared with that of patients with febrile response at bacteraemia onset. We believe that the favourable prognoses of patients with higher iBTs are attributable to increased humoral and cellular immunity.…”
Section: Discussionsupporting
confidence: 92%
“…Along these lines, previous ED-based studies showed that hyperthermia and high blood pressure did not seem to be strongly associated with adverse events in the ED. 32,33 We defined an EDICAS of 3-5 as a medium-risk category, which may be used to flag patients needing an urgent physician assessment, particularly those who are initially triaged to lower levels. We also defined an EDICAS of 6 or above as a high-risk category as it corresponded to a specificity of 98% and a positive likelihood ratio of 12.7, both of which could raise the probability PPV, positive predictive value; NPV, negative predictive value; LR+, positive likelihood ratio; LR-, negative likelihood ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, previous ED-based studies showed that hyperthermia and high blood pressure did not seem to be strongly associated with adverse events in the ED. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Our study further demonstrated that the hypoinflammatory state usually persisted, at least in the ED, and predicted worse outcomes. On the other hand, a study has reported that hyperthermic patients in the ED received more antibiotic therapy, and thus had lower mortality compared with normothermic patients (25).…”
Section: Discussionmentioning
confidence: 98%